Implementation of Micro Business Productive Assistance for UMKM as an Effort to Grow a Sustainable Economy - Siti Maria; Diana Lestari; Siti Amalia (Universitas Muhammadiyah Yogyakarta, 2022)
This article discusses the Analysis of Micro Business Productive Assistance (BPUM) for Micro, Small, and Medium Enterprises (UMKM) as an effort to Grow and Develop a Sustainable Economy in East Kalimantan, so to explore the topics discussed, this research uses literature study research sourced from theories relevant to the problems in this study, Findings in this study that Micro Business Productive Assistance provides stimulus effective in improving and strengthening UMKM institutions amid the problems faced such as the Covid-19 pandemic and previous UMKM problems. The findings in this study make the conclusion that BPUM is effective in a certain time but in the context of sustainable economic growth, UMKM receiving BPUM are not always able to rely on this program. This is because this program is not sustainable and follows the system of state financial mechanisms available. This means that UMKM must be able to maximize BPUM optimally and be able to make their services progress and sustainable. The massive economic growth of UMKM, followed by strengthening through a creative economy and targeting aspects of the global market, will make UMKM able to survey all issues. So that the impact caused by the existence of a sustainable and creative economy UMKM in the digitalization era makes economic growth in the region increase with the addition of Gross Domestic Product (GDP) and National Income (PN). For BPUM assistance to East Kalimantan UMKM as a whole in 2021 has been realized effectively and optimally, but in 2022 there are several mechanisms that are still not running in several regions and there is a reduction in budget assistance deposited into UMKM